A CASE OF LOWER ABDOMINAL LINEA ALBA HERNIA - MATSUDA, Mituhiro; TSURUOKA, Yuko; SUGANO, Masahiko; TSURUMARU, Masahiko; SAKAMOTO, Kazuhiro; KAMANO, Toshiki (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
A 42-year-old woman undergone a transvaginal hysterectomy two years earlier was seen at the hospital because of a lower abdominal mass. A soft tumor with the size of about 3 cm was palpated in the lower middle abdomen. The reduction of the mass was easily possible by hand. Ultrasonography and abdominal CT revealed that the tumor with the size of about 3 cm seemed the greater omentum protruded through a defect of the linea alba in the lower abdomen. A diagnosis of linea alba hernia was made, and an operation was performed. The preperitoneal fat and hernial sac were recognized in the lower middle abdomen. The hernial sac was dissected out, and then the hilus of the hernia was closed. There have been no signs of recurrence up to now. Linea alba hernia is a rare condition, and only 66 cases including our case have been reported in Japan. Of the 66 cases, only seven cases were of linea alba hernia occurred in the lower abdomen. In combination with the fragility of the linea alba, abdominal high pressure due to pregnancy and delivery, and previous hysterectomy, the hernia might occur in this case. We report this case with a review of linea alba hernia in Japan.